2003
DOI: 10.1038/sj.jhh.1001551
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure and left ventricular structure and function in relation to the G-protein β3-subunit polymorphism C825T in White Europeans

Abstract: The 825T allele of the G-protein b 3 -subunit is associated with increased intracellular signalling. Its association with hypertension is inconsistent. We, therefore, studied the C825T polymorphism in relation to ambulatory blood pressure as well as left ventricular structure and function in two European populations. We genotyped 248 parents and 318 offspring, enrolled in the European Project on Genes in Hypertension in Cracow, Poland (n ¼ 286) and in Novosibirsk, Russian Federation (n ¼ 280). The 24-h ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…The recent study by Siffert et al 10 reported a positive association between the T variants of the Gb-3-C825T genotype with EH in subjects coming from three areas of Germany. Subsequent report from some researchers in Europe 11,17 and Australia 12 had similar results. However, results of studies investigating the association between the GNB3 C825T polymorphism and hypertension in Japanese, 18 Tanwan Hans, 19 Canadian Oji-cree, 13 and African Americans 14 have proved conflicting.…”
Section: Discussionsupporting
confidence: 55%
“…The recent study by Siffert et al 10 reported a positive association between the T variants of the Gb-3-C825T genotype with EH in subjects coming from three areas of Germany. Subsequent report from some researchers in Europe 11,17 and Australia 12 had similar results. However, results of studies investigating the association between the GNB3 C825T polymorphism and hypertension in Japanese, 18 Tanwan Hans, 19 Canadian Oji-cree, 13 and African Americans 14 have proved conflicting.…”
Section: Discussionsupporting
confidence: 55%
“…In our cohort considered as a whole, the cognitive pattern was mildly worse than expected from Italian normative data [35] probably because the TT subjects were more represented in our cohort (15%) than in the European population (8.1–8.4%) [41, 42]. The unfavorable cardiovascular pattern which is typical of the LEOGRA population [20, 21], and which in part derives in turn from the T mutation [2], could also account for impaired cognition.…”
Section: Discussionmentioning
confidence: 97%
“…Polymorphisms of candidate genes on different chromosomes in diverse pathways (e.g., the angiotensin converting enzyme (ACE) [9], major histocompatibility complex [10], guanine nucleotide-binding protein (GNB3) [11], insulin-like growth factor (IGF-1) [12], and neuropeptide Y (NPY) genes [13]) have been associated with LV mass. However, other studies have failed to replicate the association with some of these polymorphisms (e.g., ACE [14], GNB3 [15]). Evidence of association of other echocardiographic measures of LV geometry with various polymorphisms is nearly equally abundant and similarly contradictory [16, 17].…”
Section: Introductionmentioning
confidence: 99%